The cost-effectiveness analysis of single-tablet efavirenz-based regimen among HIV-1 infected adults in China - Zhang, Haijun; Kong, Yuhao; Chen, Haotian; Luo, Sitong; Fan, Pengyang; Li, Zhihui (Frontiers in Public Health, 2025)
IntroductionIn 2018, the Chinese Guidelines for Diagnosis and Treatment of HIV/AIDS recommended the adoption of the efavirenz 400 mg-based TLE (tenofovir disoproxil fumarate (TDF) + lamivudine (3TC) + efavirenz (EFV)) regimen as the primary first-line treatment for ART-naive HIV-1 infected adults in China. However, the cost-effectiveness of different TLE treatment strategies remains uncertain. This study aimed to evaluate the cost-effectiveness of various TLE treatment strategies for ART-naive HIV-1 infected adults in China.MethodsA decision-tree Markov state transition model was employed to assess the cost-effectiveness of various TLE treatment strategies over a 10-year timeframe, from a societal perspective. Input parameters were obtained from published literature and publicly accessible information. Local data from the latest sources were used as input parameters whenever possible. The main outcome measure was the incremental costs per quality-adjusted life years (QALYs) gained. Sensitivity analyses were performed to investigate model uncertainties and determine break-even prices.ResultsCompared to the multiple-tablet regimen (MTR) consisting of efavirenz 400 mg-based TLE (TLE400) and efavirenz 600 mg-based TLE (TLE600), the single-tablet regimen (STR) of TLE400 exhibited a 10-year cost of 130733.8 CNY (compared to 122939.7 CNY and 126184.3 CNY, respectively) and an expected QALYs of 6.45 (compared to 6.27 QALYs and 6.32 QALYs, respectively) per HIV-1 patient in China. Consequently, the incremental cost-effectiveness ratios (ICERs) were 41021.6 CNY/QALY gained (equivalent to US 6071.2 per QALY gained) and 34996.2 CNY/QALY gained (equivalent to US 5179.4 per QALY gained) for TLE400 STR compared to TLE400 MTR and TLE600 MTR, respectively. The ICER for TLE400 MTR compared to TLE600 MTR was 54076.7 CNY/QALY gained (equivalent to US 8003.4 per QALY gained). Deterministic sensitivity analysis indicated that adherence rates to ART had the most significant influence on all three strategies. In probabilistic sensitivity analysis, TLE400 STR demonstrated a 71.4% probability of being highly cost-effective nationwide, based on the one-time national-level GDP per capita.ConclusionIn the context of treating HIV-1 infected adults in China, the STR of TLE400 demonstrated cost-effectiveness when compared to both the MTR of TLE400 and the MTR of TLE600.